Apparent Digestibility Coefficients of Selected Plant Protein Feed Ingredients and Feeds for Coho Salmon (Oncorhynchus kisutch) Postsmolts Cultured in Fresh Water - Baobin Lu; Leyong Yu; Hairui Yu; Abdur Rahman; Chengyu Ma; Xiaojing Wu; Lingyao Li; Shahid Sherzada; Nimra Hussain (Aquaculture Nutrition)
The aquafeed industry relies on fish meal as a major protein source, but its use raises economic and environmental concerns, prompting the search for sustainable alternatives. This study compared the apparent digestibility coefficients (ADCs) of dry matter (DM), energy, protein, phosphorus, lipids, and amino acids (AAs) for selected protein ingredients in Coho salmon. For this purpose, one reference and seven test diets corresponding to beer yeast (BY), corn gluten meal (CGM), cottonseed meal (CSM), peanut meal (PNM), rapeseed meal (RSM), soybean meal(SBM), and soy protein concentrate (SPC) were formulated with the ratio of 70:30 of the reference diet and one of the test ingredients. 1200 fish were randomly distributed into 24 glass aquaria (each with a diameter of 3.0 m and a depth of 1.5 m, water volume 8.5 m³) with three aquaria per experimental diet (total n = 50 ∗24 = 1200). The experiment lasted for 8 weeks. The results indicated that ADCs of DM ranged from 43.34% for RSM to 72.90% for SPC. Similarly, the highest ADCs of crude protein (72.69% to 86.76%), lipid (77.09% to 87.72%), and gross energy (74.12% to 55.44%) were observed in SPC, and the lowest were found in RSM. However, the ADCs of phosphorus ranged from 36.14% (RSM) to 47.35% (SBM). The ADCs of proximate nutrients for BY, CGM, PNM, SBM, and SPC were significantly higher (p <0.05) than other protein ingredients (RSM, CGM). Similar patterns of digestibility were observed for individual AAs of the test ingredients. Overall, the diet containing SPC appeared to be more suitable and compatible with the reference diet. Conversely, PNM, BY, SBM, and CGM showed some potential as aquafeed ingredients, whereas CSM and RSM appear to be the least viable options. Such information aids in better feed formulation by focusing on nutrient absorption rather than raw ingredient composition.